Analisis Pengaruh Tingkat Kemiskinan, Pengeluaran Pemerintah dan Kesempatan Kerja terhadap Indeks Pembangunan Manusia Provinsi Jambi Tahun 2018-2025 - Nur Afriza Nauli; Etik Umiyati; Helen Parkhurst (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study examines the effects of the poverty rate, government expenditure, and employment opportunities on the Human Development Index (HDI) of regencies and municipalities in Jambi Province during the 2018–2025 period. The study used secondary panel data comprising time-series data from 2018 to 2025 and cross-sectional data from eleven regencies and municipalities. Panel data regression with the Fixed Effect Model (FEM) was employed based on the Chow, Hausman, and Lagrange Multiplier tests. The results show that the poverty rate has a negative and significant effect on HDI (β = −1.260869, p = 0.0029), indicating that an increase in poverty reduces human development. Government expenditure has a positive and significant effect on HDI (β = 4.57 × 10⁻¹², p = 0.0009), while employment opportunities also positively and significantly influence HDI (β = 7.65 × 10⁻⁵, p < 0.001). Simultaneously, all independent variables significantly affect HDI (F = 42.82617, p < 0.001). The coefficient of determination (R² = 0.882678) indicates that 88.27% of the variation in HDI is explained by the model. These findings suggest that reducing poverty, increasing public expenditure, and expanding employment opportunities are essential strategies for improving human development in Jambi Province.